Estudo do uso do software Microisis nas bibliotecas e centros de Informação de Belo Horizonte - Cléia Márcia Gomes Amaral (2000)
Study of the use of Microlsis in 32 libraries and information centers of Belo Horizonte. The software was developed by UNESCO, being distributed in Brazil by ffilCT. It has as objective to offer a low cost software that assists to the needs of automation of libraries and centers of information of the developing countries. The work attempted to imcover how the libraries of Belo Horizonte use this software, attention to the construction and management of the data bases and, if Microlsis is attending the needs of the libraries users' automation. The work is composed of introduction, literalure review about automation of libraries in Brazil and foreign libraries, historical view of Microlsis with origin, concept, and resources of the software. The research methodology of is presented, followed by presentation of results, data analysis and conclusion of the research. lt wasobserved: that the resources of the software are well known by its users, that the necessarycares are observed in the entrance and indexation of the data to guarantee the consistency and that MicrosIsis attends the needs ofautomationofthe libraries ofBelo Horizonte